The Karstic Corrosion in Al-Dalieh region (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Al-Dalieh region lies in the Western slopes of the Syrian coastal mountains series,. and the area is lies near the Assian-African fault, that caused rising The oldest Jurrasic Layers which formed the tops of the mountains, while the newest Kretassic Layers lied on the slopes, In addition there are three-Nugeen Layers covers a small area .And as a result of permeability of these rocks, the water go towards underground through holes This lithological and hydrogeological installation caused forming distinctive karstic surface and groundwater forms by the dissolution and melting of the limestone rocks. So this research seeks to study the characteristics which returned to the Karstic Corrosion in Al-Dalieh region and knowing the Rate of Karastic Corrosion in the water of Al-Dalieh spring, and thus estimate the time of the emergence of the karstic forms in this region.